Mampukah Kecerdasan Spiritual Memoderasi Hubungan Faktor Demografi dalam Mengelola Keuangan Pribadi Mahasiswa? - Nurul Humairo; Indah Yuliana (Esensi: Jurnal Bisnis dan Manajemen, 2019)
This study examines the effect of demographic factors on personal financial management with spiritual intelligence as a moderating variable. The sampling technique is proportionate random sampling, the number of research samples 388 students of State Islamic University Maulana Malik Ibrahim Malang. The test results indicate an influence on personal financial management. The positive influence of demographic factors with age characteristics on personal financial management. As for the characteristics of the sex found no influence on personal financial management. Spiritual intelligence as a moderating variable is able to strengthen the relationship between demographic factors and personal financial management of State Islamic University Maulana Malik Ibrahim Malang students. Education providers to design finance education patterns can use the implications of this study for students.